DINAMIKA AKTOR DALAM UPAYA PEMBENTUKAN KABUPATEN KEPULAUAN KUNDUR PROVINSI KEPULAUAN RIAU TAHUN 2011-2014 - Sanjaya "; Ali Yusri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research is aimed at,first,identifying the actors involvedin either directly or indirectlyas well as the actors’ interests in the effort of establishing Kepulauan Kundur District. Second,it is also aimed at identifyingthe actors dynamics that occur in the processof Kepulauan Kundur District’s establishment. The main problem in this research wasthe discrepancy between what had been planned and the implementation in reality in which it caused movementsthataffectedoneanother. It means that there were pros and conssituations regarding the territorial reform of Kundur District that causedsome dynamics. The writer used actor theory, politics elite, and dynamics concept as the literature reviews. The research used a qualitative method of a descriptive research. The data gathered in this research were primary and secondary data that were collected through interviews(with the informan who know and understand about thesubject matters), documentations, and observations.The result showed that:first, there were actors involved in the agenda with diffference interests regarding the establishment of Kepulauan Kundur District, including the ones who supportedthe territorial reform of Kepulauan Kundur District and the ones who did not. Second, the actors dynamics began when Moro Sub-district stated to stay in Karimun District territory hence caused the movements between the actors thataffected each other’s actions. The carried outactions taken by the actors were in different ways so that it seemed that the effort of Kundur’s territorial reform did not work well.Key words: Actor, Politics Elite, Actors Dynamics